Linking Heterotrophic Microbial Activities with Particle Characteristics in Waters of the Mississippi River Delta in the Aftermath of Hurricane Isaac - Ziervogel, Kai; Osburn, Christopher; Brym, Adeline; Battles, Jessica; Joye, Samantha; D'souza, Nigel; Montoya, Joseph; Passow, Uta; Arnosti, Carol (Frontiers in Marine Science, 2016)
Riverine runoff often triggers microbial responses in coastal marine environments, including phytoplankton blooms and enhanced bacterial biomass production that drive the transformation of dissolved and particulate organic matter on its way from land to the deep ocean. We measured concentrations and characteristics of particulate organic matter (POM), concentrations of dissolved organic carbon (DOC), and bacterial community abundance and activities in the water column at three sites near the Mississippi River Delta two weeks after Hurricane Isaac made landfall in late August 2012. River plumes had salinities of >30 PSU and high levels of DOC (210-380 µM), resulting from the storm surge that pushed large quantities of marine waters upstream. Relatively high concentrations of phytoplankton POM and low levels of microbial exopolymeric particles (TEP and CSP) suggested that storm-induced riverine discharge triggered the development of phytoplankton blooms that were in their initial stages at the time of sampling. Surface water POM had C/N ratios of 5-7 and strong protein-like fluorescence signals in the base-extracted POM (BEPOM) fraction at the two sites closer to the river mouth (Stns. TE and MSP). Freshly produced POM triggered a twofold increase in heterotrophic bacterial biomass production (3H-leucine incorporation) and a fourfold increase in bacterial peptide hydrolysis (activities of leucine-aminopeptidase). In contrast, elevated DOC concentrations coincided with only moderate bacterial community activity, suggesting that heterotrophic bacterial metabolism near the Mississippi River Delta in the aftermath of Hurricane Isaac was more closely linked with autochthonous primary production.